Expanding the keratin mutation database: novel and recurrent mutations and genotype-phenotype correlations in 28 patients with epidermolytic ichthyosis - Arin, Meral Julia; Oji, V.; Emmert, S.; Haußer-Siller, Ingrid; Traupe, H.; Krieg, T.; Grimberg, G. (British journal of dermatology, 2011)
Background Epidermolytic ichthyosis (EI) is a hereditary keratinization disorder caused by mutations in the keratin 1 (KRT1) or keratin 10 (KRT10) genes. In most cases of severe EI, heterozygous single point mutations are found at the highly conserved helix boundary motifs of KRT1 and KRT10 that play a critical role in filament formation. The presence of palmoplantar keratoderma suggests KRT1 mutations, whereas KRT10 mutations in most instances give rise to the nonpalmoplantar variants. Objectives To identify the underlying mutations in patients with EI and to correlate genotype and phenotype. Methods Mutation analysis was performed in 28 patients with EI by direct sequencing of KRT1 and KRT10 genes. Results We identified 14 different mutations, of which four have not been published previously. Conclusions Identification of novel mutations and genotype-phenotype correlations in EI allows improved understanding of disease pathogenesis as well as better patient management.